2017
DOI: 10.1007/s10877-017-9979-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the marvelous™ three-way stopcock on the natural frequency and damping coefficient in blood pressure transducer kits

Abstract: Two types of Planecta™ ports are commonly used as sampling ports in blood pressure transducer kits: a flat-type port (FTP) and a port with a three-way stopcock (PTS). Recently, a new type of three-way stopcock (Marvelous™) has been released as a Planecta™ counterpart, but its effects on the frequency characteristics and reliability of blood pressure monitoring have not been investigated. We assessed the influence of the Marvelous™ stopcock on the frequency characteristics of the pressure transducer kit. The ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Through 2018, we also saw a few papers in the area of technical development. Fujiwara and colleagues [36] validated a newly developed three-way stopcock and showed that the natural frequency and damping coefficients were not altered to a clinically relevant extent even when three stopcocks were inserted serially before the pressure transducer. The new stopcock appeared a safe substitute for existing stop-cocks in terms of the frequency response, while also offering improved features to help preventing contamination.…”
Section: Technical Developmentsmentioning
confidence: 99%
“…Through 2018, we also saw a few papers in the area of technical development. Fujiwara and colleagues [36] validated a newly developed three-way stopcock and showed that the natural frequency and damping coefficients were not altered to a clinically relevant extent even when three stopcocks were inserted serially before the pressure transducer. The new stopcock appeared a safe substitute for existing stop-cocks in terms of the frequency response, while also offering improved features to help preventing contamination.…”
Section: Technical Developmentsmentioning
confidence: 99%